Synthesis and Characteristic of Organic-Inorganic Hybrid Materials Cu2(OH)(4-x)(C10H17O2)x·zH2O - Zheng, Deshan (Asian Journal of Chemistry, 2012)
In this paper, the ligand 3,7-dimethyl-6-octenoic acid was grafted in the inorganic groups layered hydroxy copper acetate through an anion exchange reaction. Combination of XRD, elemental analysis and TGA, the structure of these hybrid materials have been studied and characterized. The infrared, ultraviolet properties and magnetic spectra of these hybrid materials also discussed.